Peran Mahasiswa Dalam Pencegahan Bencana Asap Melalui Kukerta Terintegrasi Universitas Abdurrab di Desa Dayun - Diki Arisandi Diki; Amir Syamsuadi; Seri Hartati; Liza Trisnawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Dayun is one of the villages in the Siak Regency. Every year, the thread of fire and haze disaster always occurs and causes economic losses and health impairment of the villagers. This Community service was in partnership with the Regional Disaster Management Agency of Siak Regency. Through the integrated Community service program for the student of Abdurrab University, collaborating with the Lecturer’s Community Service program, the students from various majors are taking action to the community service in Dayun Village. The activities were to transfer the knowledge to the community and designing an early detection system. During the program, the students were creating media designs such as videos and pamphlets. Some Informatics students were developing a web-based application for early detection. The results were presented at the Regional Disaster Management Agency of Siak Regency and acquired positive responses from the participants.